An automatic road vector extraction method from maps - Nagao, T.; Agui, T.; Nakajima, M. (Pattern Recognition, 9th International Conference on, 1988: Proceedings, 2003)
An automatic road extraction method for 1/25000 scaled maps of Japan is presented. The method is applied to the automatic input of map data in a computer and also to recognition of line drawings. In the first process, the feature points of roads are calculated on the center lines of roads, and short vectors are made by connecting the feature points. Some of the vectors, corresponding to roads, are joined, and others are regarded as noise and removed in subsequent processes. The algorithm of this method is described, and experimental results applied to urban maps are shown.< >